Ownership Structure and Performance of Small Medium Size Enterprises in Sri Lanka. - Koperunthevy, K.; Pathirannahelage, C.R.R. (Vavuniya Campus of the University of Jaffna., 2009)
This research investigates the relationship between ownership structure performance of Small and Medium size Enterprises (SMEs). Ownership structure of Enterprises has important role to determine firms’ performance. In Sri Lanka share ownership in listed companies is highly concentrated and produces significant and consistent results in respect of accounting performance. Therefore, this study focuses on how ownership structure of SMEs affects its performance. The SMEs’ ownership structures of family ownership, managerial ownership and owner manger were investigated in relation to Return on Total Assets _ net income (ROA_ net income), Return on Total Assets _ lagged (ROA_ lagged) and Tobin Q by using the cross sectional Ordinary least - square (OLS) regression model with the period of 2000 to 2004. The sample covers 32 SMEs in Vavuniya district. The study conclus that the family ownership firms are more profitable than other types of ownership structures and managerial ownership has negative impact on firms’ performance. Further, the study shows that the ownership structures in the SMEs have a significant influence on firms’ performance.
Keywords: Corporate governance; Ownership; Structure; Agency theory.